Medial canthal reconstruction with multiple local flaps() - Ogino, Akihiro (JPRAS Open, 2017)
BACKGROUND: It is often difficult to reconstruct comparatively large defects in the medial canthal region. The authors have performed reconstruction with multiple local flaps in 4 medial canthal defects after resection of malignant skin tumors. METHOD: The defects exceeded the medial canthal region, extending to the upper eyelid and the lower eyelid. The medial canthal defect was covered by transposition of a glabellar flap, the upper eyelid defect was covered by an upper eyelid myocutaneous advancement flap, and the lower eyelid defect was covered by a cheek rotation flap. Then the donor site of the glabellar flap was covered by a Rintala flap. RESULTS: There was no recurrence in any of the cases, and good results were obtained. One case showed mild linear contracture, but the patient did not want corrective surgery. CONCLUSION: This method is somewhat complicated compared to reconstruction with a single flap, but it is a combination of standard local flaps and is a simple reconstructive procedure. By adding additional resection, the suture line is consistent with the border of the facial unit, so postoperative scarring is inconspicuous. This technique is aesthetically useful because of the continuity of colour and texture resulting from the use of adjacent flaps.